2015
DOI: 10.1080/01694243.2015.1037382
|View full text |Cite
|
Sign up to set email alerts
|

Self-bonding of PEEK for active medical implants applications

Abstract: In an effort to select the best possible medical grade of polyether ether ketone (PEEK) for active medical implants application, it was necessary to inspect surface thermodynamic properties of different grades and correlate with self-bonding (autohesion) strength. Autohesion is the process of choice for encapsulating active medical implants made of PEEK. Temperature modulated DSC was used to investigate crystallinity and thermal events of range of medical grade PEEK (semicrystalline, amorphous, semi-crystallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The crystallinity index is an important parameter for polymers, as it affects many physical properties, including polymer density, melting point, hardness, elastic modulus, tensile strength, stiffness and permeability. Polymer crystallinity is also supposed to influence autohesion phenomena, although self‐bonding highly depends on processing parameters, including bonding method, working temperature, pressure and time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystallinity index is an important parameter for polymers, as it affects many physical properties, including polymer density, melting point, hardness, elastic modulus, tensile strength, stiffness and permeability. Polymer crystallinity is also supposed to influence autohesion phenomena, although self‐bonding highly depends on processing parameters, including bonding method, working temperature, pressure and time.…”
Section: Resultsmentioning
confidence: 99%
“…The final bonding configuration is reported in Figure b. Polymer specimens were maintained in the press at 200°C and 3 MPa operating pressure for 2 h or 7.5 h. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For semi-crystalline polymers, it is commonly admitted that the effective bonding starts from melting temperature, the presence of crystalline zone prevents the macromolecules of the amorphous phase from moving to the neighborhood. However, some studies show that a physical bond is formed between two surfaces of amorphous PEEK at temperature below its melting temperature [9][10][11][12][13]. Rationally, Boiko noticed in 2001 that the crystallization hinders auto-adhesion phenomenon applied to PEEK [14].…”
Section: Kinetics Of Cold Crystallization Of Peekmentioning
confidence: 99%
“…After performing isothermal bonding experiments in the vicinity of the glass transition temperature for amorphous and semi-crystalline PET, it was found that the strength values of bonded semi-crystalline specimens were one order of magnitude smaller than the strength of bonded amorphous specimens. This was explained not only by the immobility of the crystalline fraction, but also since a part of the amorphous polymer chains is firmly fixed by the surrounding crystalline regions, which severely limits the penetration depth of the polymer chains into the adjacent substrate (Boiko et al, 2001;Awaja and Zhang, 2015). As a result, the crystallinity of the polymer directly influences the concentration of mobile chain ends at the interface.…”
Section: Non-isothermal Healing Of Semi-crystalline Polymersmentioning
confidence: 99%